THE USE OF PROJECT-BASED LEARNING IN FOREIGN LANGUAGE TEACHING - Решетняк, Ірина (SWorldJournal, 2026)
The article explores the use of project-based learning as an effective methodology for teaching foreign languages at the university level. It examines various types of projects, including informational, research, game-based, creative, and practical, and h